Effect of intrauterine Allium sativum extract on recovery and conception rate in dairy cows with subclinical endometritis - Yildiz, Atilla (Indian Counc Agricultural Res, 2016)
The current study was designed to investigate the therapeutic effectiveness of Allium sativum (garlic) extract infusion on recovery and conception rate in cows with subclinical endometritis. Cows (42) with subclinical endometritis were randomly divided into 2 equal groups. In treatment group (group T), cows received a single intrauterine administration of 10 ml garlic extract mixed with 40 ml saline. In the cows of control group (group C), no intrauterine treatment was administered. Samples were collected again from the all animals of both groups on day 14 after therapy and the same laboratory tests were repeated. The cows were artificially inseminated at the following estrus. 10 (23.8 %) out of 42 cows had subclinical endometritis without bacteria in the uterus; however majority of cows with subclinical endometritis were positive for bacterial infection (76.2%). Bacterial load in group T was significantly lower as compared to both pre-treatment and group C. The cure rate for group T and C was 100.0 and 19.0%, respectively. The conception rates in groups T and C were 52.4 and 14.3%, respectively. Our results indicated that the intrauterine use of garlic extract can decrease endometrial inflammation and bacterial load, and consequently an increase in the conception rate.
Keywords: Cow; Garlic extract; Subclinical endometritis